ELEMEN LOKAL PADA PAPAN NAMA RESTORAN WARALABA JEPANG DI DENPASAR - Aritonang, Betty; Meilantari, Ni Luh Gede; Sudipa, Made Henra Dwikarmawan (Jurnal SORA - Pernik Studi Bahasa Asing, 2023)
The emergence of Japanese restaurants in Indonesia, including franchise networks, companies with foreign and domestic capital, demonstrates that Japanese food is being globalized. Globalization makes it easier for outside culture to infiltrate local life. Events in other worlds can easily be imitated by other parts, resulting in homogeneity in every community's life. Local elements must emerge as markers or characteristics of a specific area as homogeneity is strengthened. Glocalization is the concept of combining global and local cultures. Cultures from outside are then adapted to local culture, resulting in hybridity or unification of the local and the global. Two levels of analysis will be used in researching the glocalization of Japanese franchise restaurant sign boards in Denpasar: the language code type stage and the psychological stage. A descriptive qualitative research method was employed. According to the findings of the analysis, the process of glocalization on the nameplates of Japanese franchise restaurants in Indonesia is carried out by 'transliterating,' or changing the writing from Japanese to Latin letters. Some restaurants include words or sentences that help locals identify the restaurant's characteristics. Regardless, glocalization is done to attract Indonesian consumers.